Kajian Maqashid Syari’ah dalam Undang-undang Nomor 3 Tahun 2020 tentang Pertambangan Mineral dan Batubara di Indonesia - Fikri, Ahmad Lutfi Rijalul (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2023)
Maqashid Sharia, as a principle in lawmaking, aims to harmonize Islamic teachings with various contexts, including their compatibility with modern circumstances. The embodiment of Islamic values can be observed in the implementation of Law Number 3 of 2020 concerning Minerals and Coal, which has recently sparked public debate. A Sharia maqashid analysis is essential as this law directly impacts the benefits and potential harms stemming from its enforcement. The research findings indicate that the Minerba Law in Indonesia incorporates Maqashid Sharia principles, aligning with the objectives of Sharia in law formulation and stipulation, particularly in promoting public welfare (Mashlahah 'Ammah). However, the Minerba Law also faces critique regarding certain contentious articles which have raised concerns among legal experts.